Synthesis, Crystal Structure and DFT Studies of 4-(1-Benzyl-5-methyl-1H-1,2,3-triazol-4-yl)-6-(o-tolyl)pyrimidin-2-amine - Murugavel, S.; Madhanraj, R.; Nagarajan, Sangaraiah; Ponnuswamy, Alagusundaram (Asian Journal of Chemistry, 2015)
The compound (I), 4-(1-benzyl-5-methyl-1H-1,2,3-triazol-4-yl)-6-(o-tolyl)pyrimidin-2-amine (C21H20N6), was synthesized and structurally characterized by elemental analysis, 1H NMR and 13C NMR and single crystal X-ray diffraction. The compound crystallizes as a colourless needle shaped in the monoclinic system, space group P21/n with cell constants: a = 11.2942(16) Å, b = 16.1209(18) Å, c = 10.6253(14) Å, a = g = 90°, b = 106.898 (5)°, V = 1851 (4) Å3, Z = 4. In the compound, the triazole and the pyrimidine rings are essentially planar. The molecular conformation is stabilized by an intramolecular C-H…N hydrogen bond, which generates an S(6) ring motif. The crystal packing is stabilized by intermolecular N-H…N and C-H…p hydrogen bonds thereby generating a three-dimensional supramolecular network. The molecular geometry was also optimized using density functional theory using (DFT/B3LYP) method with the 6-311G (d, p) basis set and compared with the experimental data.